1996
DOI: 10.1111/j.1440-6055.1996.tb01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature Regimes on the Development, Survival and Emergence of Culicoides brevitarsis Kieffer (Diptera: Ceratopogonidae) in Bovine Dung

Abstract: Culicoides brevitursis is a biting midge and a vector of several viruses affecting livestock in Australia. An emergence chamber for collecting Culicoides spp. from dung was evaluated to determine its suitability for the study of C. brevitursis developing in dung at different temperatures in the laboratory. It enabled experiments to be carried out in the natural breeding medium, relative humidity to be maintained at high levels and temperature through the dung to be stabilised at treatment temperatures relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…The activity period of adult C. maculatus during the year was observed longer than that of C. oxystoma at same collection sites and extended to late autumn or early winter (Ueno et al 1956;Yanase, personal communication). It is known that temperature also has an impact on the developing stage of Culicoides species (Kitaoka 1982;Bishop et al 1996) and, thus, the presence of adult insects. Further studies would be necessary to elucidate the particular influence of temperature for the different distribution of these two species.…”
Section: Discussionmentioning
confidence: 99%
“…The activity period of adult C. maculatus during the year was observed longer than that of C. oxystoma at same collection sites and extended to late autumn or early winter (Ueno et al 1956;Yanase, personal communication). It is known that temperature also has an impact on the developing stage of Culicoides species (Kitaoka 1982;Bishop et al 1996) and, thus, the presence of adult insects. Further studies would be necessary to elucidate the particular influence of temperature for the different distribution of these two species.…”
Section: Discussionmentioning
confidence: 99%
“…temperature, precipitation) that can influence distribution, abundance and vectorial capacity in Culicoides. In the main, it would seem clear that, in the future, increased temperatures will lengthen the Culicoides biting season, quicken the larval developmental cycle (thereby increasing the number of generations completed) (58,59) and, importantly, accelerate vector-biting and extrinsic virus replication rates. At the more local farm level, the interplay between climatic and environmental variables (including temperature, relative humidity, light intensity, wind speed and the like) is complex, with changes in optimality from one species to the next.…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…Climate change, and more specifically alterations in temperature, may affect larval stages of some Culicoides species. Allingham (1991) and Bishop et al (1996) demonstrated that Culicoides brevitarsis Kieffer emerge between 17-36 °C, with most emergence occurring in the 25-36 °C range. They also showed that average temperature in the field prior to their experiment starting, i.e.…”
Section: Lifecyclementioning
confidence: 99%